(3hajGJ GdCcGHQ aj GdbQf GdYGTQs - (3eMj GdOjf YHO GdbGOQ Hf TjN YHO Gddg GdYjOQhS GdYdhjs; (3GdYjOQhS , YHO GdbGOQ Hf TjN Hf YHO Gddg Hf TjN Hf YHO Gddg Gdjefj, eMjj GdOjf , CHh HcQ,J (B1038 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf s
(3BNQgG (B:s
(3hgPG BNQ eG jSQ Gddg LeYg ef GdJGQjN GdeNJUQ GdLGeY s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B288s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B419 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GQjN (B- (3bSe (B3 - (3U (B337 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs